A note on Wh-islands and Finite Control in Brazilian Portuguese (Algumas observações sobre Ilhas-que e controle finito em Português Brasileiro) - Nunes, Jairo (Estudos da Língua(gem), 2010)
This paper discusses Ferreira’s (2000, 2004, 2009) claim that selective intervention effects in wh-island constructions in Brazilian Portuguese provide evidence for analyzing its referential null subjects as traces of A-movement. Based on the fact that intervening traces of wh-phrases in [Spec,CP] never prevent A-movement of an embedded subject out of an embedded declarative clause, I argue that a filled [Spec,CP] does not block A-movement either. Reinterpreting Ferreira’s data, I propose instead that A-movement is blocked if there is an intervening [Spec,TopP]. KEYWORDS: finite control, hyper-raising, wh-islands, movement theory of control, Brazilian Portuguese. RESUMO Este trabalho discute a proposta de Ferreira (2000, 2004, 2009) de que efeitos de intervenção em construções envolvendo ilhas interrogativas em português brasileiro fornecem evidência para analisar seus sujeitos nulos referenciais como vestígios de movimento-A. Baseado no fato de que vestígios de sintagmas-qu em [Spec,CP] nunca impedem movimento-A do sujeito encaixado de uma oração declarativa, eu argumento que [Spec,CP] também não bloqueia movimento-A. Reanalisando os dados de Ferreira, eu proponho que movimento-A é na verdade bloqueado se houver um [Spec,TopP] intervindo. PALAVRAS-CHAVE: controle finito, hiperalçamento, ilha-qu, teoria de controle por movimento, português brasileiro.